Development and use of Digital Technology when Studying of Environment - A.I. Gavrishin (Journal of Advances in Applied & Computational Mathematics, 2019)
The aim of the research is to show the possibilities of using digital classification technology in the study of patterns of formation of natural-anthropogenic systems. With the help of the original digital computer classification technology, AGAT-2 identified the types of chemical composition of mine waters in the Eastern Donbass and assessed their impact on the environment. All surveyed periods (20 years, 1966, 1992 and 2015) discovered four main types of composition of mine waters. The first type is the acidic sulphate water with high concentrations of metals Which causes the most heavy environmental pollution. The second type is formed by chloride-sulphate waters, the third by sulfatechloride to a lesser extent enriched with metals. The fourth type is formed by soda water, which may indicate the presence of oil fields in the region. An assessment of pollution of groundwater and surface water is given.